The collapse of global plastic waste trade: Structural change, cascading failure process and potential solutions. (10th September 2021) - Li, Cai; Wang, Ling; Zhao, Jinsong; Deng, Liangchun; Yu, Shuxia; Shi, Zhihua; Wang, Zhen
Abstract: The collapse of the plastic waste trade (PWT) amplifies the threats of mismanaged plastic waste to the ecological system and human health, posing a risk as well as an opportunity to the global circular economy. Although trade barriers in the PWT continue to impact waste management systems, there are few analyses that propose global mitigation strategies in response to trade fluctuations. Here, we show that most countries have been overloaded with plastic waste compared to their ordinary capacity since China's import ban in 2017. We apply a cascading failure model to quantify the collapse process worldwide and find that 183 countries become overloaded as this collapse cascades, with nearly 6% of countries experiencing over 1.5 times their ordinary load. However, this overload could be greatly alleviated if leading countries were to sharply increase their capacity to treat plastic waste based on scenario analysis. Although waste exporters should take more responsibility and scenario analysis results show that top exporters could effectively mitigate global plastic waste levels by increasing their treatment capacity, cooperation between key exporters, importers, and intermediators has the best mitigation effects. Our analysis suggests that key countries should as soon as possible take responsibility for and cooperate in mitigating potential plastic waste pollution related to trade fluctuations. Highlights: Many countries show plastic waste overloading due to China's import ban. Structural change of plastic waste trade could lead cascading failure worldwide. Overload situation will be greatly alleviated, if leading countries work for it. The cooperation strategy has the best mitigation effect.